Relate North 2024: New Genre Arctic Art Education : Felted Futures, 2024 - Hernandez Cervantes, Fabiola; Ahmadi, Haniel; Abolfazli, Dorsa; Arrafani, Fian (Lapin yliopisto, 2024)
Felted wool, 150 x 100cm, photo series (printed collage, 8 pieces A4) Felted wool, 150 x 100cm, photo series (printed collage, 8 pieces A4)